High-Fat and Fat-Enriched Diets Impair the Benefits of Moderate Physical Training in the Aorta and the Heart in Rats - Fernandes, Cleverson Rodrigues; Kannen, Vinicius; Mata, Karina Magalhães; Frajacomo, Fernando Tadeu; Jordão Junior, Alceu Afonso; Gasparotto, Bianca; Sakita, Juliana Yumi; Elias Junior, Jorge; Leonardi, Daphne Santoro; Mauad, Fernando Marum; Ramos, Simone Gusmão; Uyemura, Sergio Akira; et al. (Frontiers in Nutrition, 2017)
Aim: Millions of people die each year due to cardiovascular disease (CVD). A Western lifestyle not only fuses a significant intake of fat with physical inactivity and obesity but also promotes CVD. Recent evidence suggests that dietary fat intake impairs the benefits of physical training. We investigated whether aerobic training could reverse the adverse effects of a high-fat diet (HFD) on the aorta. Then, we explored whether this type of exercise could reverse the damage to the heart that is imposed by fat-enriched diet (FED). Methods: Rats were randomly assigned to 2 experiments, which lasted 8 weeks each. First, rats swam for 60 minutes and were fed either a regular diet (STD) or an HFD. After aortic samples had been collected, the rats underwent a histopathological analysis for different biomarkers. Another experiment subjected rats that were fed either an STD or an FED to swimming for 20 or 90 min. Results: The first experiment revealed that rats that were subjected to an HFD endured increased oxidative damage in the aorta that exercises could not counteract. Together with increased cyclooxygenase 2 expression, an HFD in combination with physical training increased the number of macrophages. A reduction in collagen fibers with an increased number of positive α-actin cells and expression of matrix metalloproteinase-2 occurred concomitantly. Upon analyzing the second experiment, we found that physically training rats that were given an FED for 90 min/day decreased the cardiac adipose tissue density, although it did not protect the heart from fat-induced oxidative damage. Even though the physical training lowered cholesterol levels that were promoted by the FED, the levels were still higher than those in the animals that were given an STD. Feeding rats an FED impaired the swimming protocol’s effects on lowering triglyceride concentration. Additionally, exercise was unable to reverse the fat-induced deregulation in hepatic antioxidant and lipid peroxidation activities. Conclusion: Our findings reveal that an increased intake of fat undermines the potential benefits of physical exercise on the heart and the aorta.